2016
DOI: 10.1016/j.ajhg.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

RNF213 Is Associated with Intracranial Aneurysms in the French-Canadian Population

Abstract: Intracranial aneurysms (IAs) are the result of focal weakness in the artery wall and have a complex genetic makeup. To date, genome-wide association and sequencing studies have had limited success in identifying IA risk factors. Distinct populations, such as the French-Canadian (FC) population, have increased IA prevalence. In our study, we used exome sequencing to prioritize risk variants in a discovery cohort of six FC families affected by IA, and the analysis revealed an increased variation burden for ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 78 publications
2
60
0
Order By: Relevance
“…We have shown, in CEU population, that SLC26A11 rs6565653 tags the RNF213 rs12944088 (p.H4691R) variant. Interestingly, this variant has a MAF of 0.0159 in Caucasian population and was found to be more frequent among subjects with IA (0.0365) than in healthy controls (0.0163) in the French-Canadian IA study (Zhou et al 2016). However, this result was not observed in the JPT population, because most of the variation in the RNF213 gene seems to be specific to a given ethnic background.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have shown, in CEU population, that SLC26A11 rs6565653 tags the RNF213 rs12944088 (p.H4691R) variant. Interestingly, this variant has a MAF of 0.0159 in Caucasian population and was found to be more frequent among subjects with IA (0.0365) than in healthy controls (0.0163) in the French-Canadian IA study (Zhou et al 2016). However, this result was not observed in the JPT population, because most of the variation in the RNF213 gene seems to be specific to a given ethnic background.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, this study found that ICAS patients with the common RNF213 variant were younger than those without the variant and hypothesized that this variant could lead to vascular fragility in a subset of patients, resulting in ischemic and hemorrhagic neurovascular presentations (Bang et al 2016). Studies performed in the French-Canadian population suggest that variation in RNF213 is also a risk factor for developing intracranial aneurysms (IA) (Zhou et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond conflicting reports regarding the functional role of RNF213, epidemiologic data have shown significant associations between RNF213 variants and intracranial vascular disorders including MMD, ICASO, cerebral artery dissection, and intracranial aneurysm [4,[24][25][26]. At least 24 genetic changes in RNF213 have been associated with MMD [21].…”
Section: Discussionmentioning
confidence: 99%
“…To test the risk of IA in Nunavik Inuit-specific genetic loci, we performed association tests on 8,291 coding region enriched variants identified with PBS > 0.1 in 42 unadmixed Nunavik IA cases and 62 unadmixed Nunavik controls by using a linear mixed model that accounted for individual relatedness (42). The diagnosis of IA in Inuit was described in our previous study (43). After Bonferroni correction, genomewide significance was set to P < 6.03 × 10 −6 .…”
Section: Methodsmentioning
confidence: 99%